Biochemical Changes in Jackfruit Pulp as Affected by Cold Temperature - Mortuza, MG; Talukder, SU; Haque, MR (Journal of Environmental Science and Natural Resources, 2015)
Biochemical changes of three types of jackfruit pulp stored at low temperature were analyzed to make prediction whether the pulp could be made available year round by means of cold temperature treatment. Extracted fruit juice was stored at about - 200C and the analysis was carried out at 0 day, 30 day, 60 day, 90 day, 180 day and 270 day of storage period. The results show that there are significant changes in the chemical properties of jackfruit pulp during storage. Carotene and vitamin C content decreased gradually for all the varieties up to 270 days of storage period. TSS content increased slightly during storage. Total, reducing and non-reducing sugar contents were almost stable throughout the storage period. TA for all the varieties decreased and pH values increased. DOI: http://dx.doi.org/10.3329/jesnr.v7i2.22215 J. Environ. Sci. & Natural Resources, 7(2): 93-97 2014